Oxidation of Disulfides to Taurine and Sulfanilic Acid Derivatives - Furtmann, Norbert; Gilberg, Erik; Spütz, Nicola; Gütschow, Michael (Synthesis, 2015)
Taurine (2-aminoethanesulfonic acid) is a representative substructure in biologically active compounds, but can raise difficulties in direct coupling reactions. In this study, the synthesis of taurine-derived sulfonic acids and analogous aromatic sulfonic acids was accomplished by a performic acid promoted oxidation of corresponding symmetrical disulfide precursors. In some of the products, the taurine or sulfanilic acid nitrogen atom is incorporated in a heterocyclic scaffold or part of a peptide bond in dipeptide mimetics.
Keywords: dipeptides; disulfides; oxidation; sulfanilic acid; sulfonic acids; taurine